Credit Risk And Internal Factors Affecting Profitability: Evidence From Indonesian Banks - Rahmadina Ardelia; Raden Aswin Rahadi (Integrasi Sains Media, 2025)
This study aims to analyse the effect of credit risk and internal bank factors on profitability in the Indonesian banking sector, focusing on institutions categorised under KBMI (Kelompok Bank berdasarkan Modal Inti) Groups 3 and 4, which are considered systemically important due to their large core capital. The research covers 2019–2023 and utilises a panel dataset comprising 13 banks, yielding 65 firm-year observations. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE) as dependent variables. The independent variables include Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Liquidity, and Bank Size. Panel data regression was conducted using EViews 12. In the ROA model, Liquidity (β = 0.026, p = 0.0198) and Bank Size (β = 0.058, p = 0.0354) significantly influence profitability, whereas NPL and CAR do not. In the ROE model, only Bank Size (β = 0.464, p < 0.001) has a statistically significant positive impact. Other variables remain insignificant. The findings underscore the importance of scale in driving profitability for major banks. Bank managers should focus on strategic growth and liquidity management, while regulators may reassess the weight of NPL and CAR in evaluating bank performance within this group. This study enriches the literature by providing updated empirical evidence on the determinants of profitability in large Indonesian banks and highlights the relative influence of internal bank attributes in a post-pandemic financial landscape.